Dialektika Relasional Dalam Penerjemahan Alquran Ke Bahasa Bali - Jumari, Jumari (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2019)
Most Muslims have not been able to understand the Al-Qur'an in Arabic well, so the translation of the Al-Qur'an in various languages as an aid to understanding is indeed important and necessary. The existence of the translation of the Al-Qur'an in Indonesian alone is not enough, because those who master the Indonesian language well, are not many. All efforts in translating the Al-Qur'an into regional languages including Balinese, should be maintained and maintained for its continuation. In the process of translating the Al-Qur'an into Balinese often has caused debate when there is a vocabulary in the Al-Qur'an that is not yet clear in meaning and meaning, or verses that have metaphorical meaning. In the science of communication, the phenomenon of the emergence of 'tension' intellectual debate that is fierce and takes a lot of time to equate perceptions and views in addressing the contentious things about words and sentences in the Al-Qur'an, we can examine through perspective or Relational Dialectical Theory. To overcome dialectical tension in translating the Al-Qur'an into Balinese, four basic strategies (responses to dialectics) have been adopted, namely; cycle replacement, segmentation, selection, and integration.